2010
DOI: 10.1155/2010/978710
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Effect of Erythropoietin on Thalassemic Blood Cells

Abstract: Because of its stimulating effect on RBC production, erythropoietin (Epo) is used to treat anemia, for example, in patients on dialysis or on chemotherapy. In β-thalassemia, where Epo levels are low relative to the degree of anemia, Epo treatment improves the anemia state. Since RBC and platelets of these patients are under oxidative stress, which may be involved in anemia and thromboembolic complications, we investigated Epo as an antioxidant. Using flow-cytometry technology, we found that in vitro treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 79 publications
(80 reference statements)
2
30
0
2
Order By: Relevance
“…Percoll-separated erythrocytes (2x10 7 /ml) were incubated with 0.4 mM 2',7'-dichlorofluorescein diacetate (DCF; Sigma-Aldrich, Germany) for 15 min at 37°C according to Amer et al [22]. For a positive control, wt erythrocytes were exposed to 2 mM H 2 O 2 for 10 min before DCF-labelling.…”
Section: Methodsmentioning
confidence: 99%
“…Percoll-separated erythrocytes (2x10 7 /ml) were incubated with 0.4 mM 2',7'-dichlorofluorescein diacetate (DCF; Sigma-Aldrich, Germany) for 15 min at 37°C according to Amer et al [22]. For a positive control, wt erythrocytes were exposed to 2 mM H 2 O 2 for 10 min before DCF-labelling.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, metabolic disturbances and oxidative stress appear to be strongly related in the etiopathogeny of type 2 diabetes. Several studies evidenced that oxidative status was improved by EPO treatment of anemia (2,11,25). EPO therapy may exert its antioxidant effect, by modulating the action of erythrocyte antioxidant enzymes such as superoxide dismutase and glutathione peroxidase (25).…”
Section: Discussionmentioning
confidence: 99%
“…EPO therapy may exert its antioxidant effect, by modulating the action of erythrocyte antioxidant enzymes such as superoxide dismutase and glutathione peroxidase (25). Also, recent results showed that EPO treatment increased the GSH levels in both erythrocytes and platelets, in β-thalassemic patients (2). However, the relationships between EPO and erythrocyte oxidative stress in elderly subjects with diabetes have been less explored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations